Relationships between plasma levels of main adaptogene hormones and EEG & HRV parameters at human with dysadaptation - Korda, Mykhaylo; Gozhenko, Anatoliy; Fihura, Oksana; Popovych, Dariya; Żukow, Xawery; Popovych, Igor (Journal of Education, Health and Sport, 2021)
Background. The immunoneuroendocrinology became the foundation of the Truskavetsian Scientific School of Balneology. The focus of research was on the relationships between EEG and HRV parameters, EEG&HRV and leukocytogram, phagocytosis, cellular and humoral immunity as well as between changes in these parameters under the influence of adaptogenic factors Truskavets’ spa. The purpose of this study is relationships between plasma levels of major adaptogene hormones and EEG&HRV parameters at human with dysadaptation. Materials and Methods. The object of observation were 10 women 33-76 y and 10 men 37-67 y without a clinical diagnosis, but with the deviations from the norm in a number of parameters of the neuro-endocrine-immune complex as a manifestation of dysadaptation. Parameters of EEG and HRV as well as hormones levels before and after a one-week course of drinking of Naftussya bioactive water registered. Results. Using the method of canonical correlation analysis, it was found that the level of triiodothyronine is determined by the constellation of 17 EEGs and 4 HRVs parameters by 87,5%. The rate of determination of the cortisol level by 14 EEGs and 3 HRVs parameters is 83,7%, and aldosterone by the other 14 EEGs and 3 HRVs parameters is 80,0%. Neuromodulation of testosterone and calcitonin levels is characterized by sexual dimorphism. With the same coefficients of determination (92,4%), the regression model for testosteroneemia in women included 15 EEGs parameters and no HRV parameters, instead testosteroneemia in men is modulated by other 11 EEGs parameters and one HRV parameter. The level of calcitonin in women is determined by 86,2% by the constellation of 9 EEGs and 2 HRVs parameters, while in men by 83,5% by the other 5 EEGs and 4 HRVs parameters. Conclusion. Plasma levels of the main adaptation hormones are accompanied by specific patterns of EEG and HRV parameters.